A new Afrotropical species of Ectopioglossa Perkins (Hymenoptera: Vespidae: Eumeninae) - Selis, Marco (Zootaxa, 2023)
A new Afrotropical species of the Old World genus Ectopioglossa Perkins, 1912, namely Ectopioglossa sudanensis Selis, sp. nov., is described from Sudan. A key to the Afrotropical species is provided.